Anti-HSV-1 agents: an update - Lv, Wenwen; Zhou, Lei; Wu, Jia; Cheng, Jishuai; Duan, Yongzhong; Qian, Wen (Frontiers in Pharmacology, 2025)
Herpes simplex virus type I (HSV-1) is a member of the α-herpesvirus subfamily and is capable of causing herpes simplex keratitis, herpes labialis, and herpes simplex encephalitis. HSV-1 is well known for its lytic infections at the primary sites and for establishing latency in the sensory neuronal ganglia, with occasional recurrent infections. To date, there are no approved commercially available vaccines, and anti-HSV-1 drugs such as specific or non-specific nucleotide (nucleoside) analogs and helicase-primase inhibitors have become the main clinical agents for the treatment of HSV-1 infections despite challenges from resistance. Therefore, development of new anti-HSV-1 compounds or therapies is key to addressing the issue of resistance. The present review provides an update on the progress made over approximately 60 years regarding anti-HSV-1 agents while also highlighting future perspectives for controlling HSV-1 infections.